2019
DOI: 10.1039/c9nr01804b
|View full text |Cite
|
Sign up to set email alerts
|

Prussian blue analogue-derived Ni and Co bimetallic oxide nanoplate arrays block-built from porous and hollow nanocubes for the efficient oxygen evolution reaction

Abstract: NixCo3–xO4 nanoplate arrays built from nanocubes were obtained, showing excellent activity towards OER.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…Hence, it is essential to find the cheaper alternatives that are more common, highly active, and stable 13 . In doing so, a key strategy to retrieve high‐performance OER catalysts hinges upon the availability of electrode materials, including carbon‐based nanomaterials, graphene, and metal oxides/selenides/sulfides 14–24 . Thus far, the scientific community is increasingly interested in porous nanostructure‐based electrode materials, given their high surface‐to‐volume ratio, large and well‐defined pore structure, and even distribution of available active sites.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is essential to find the cheaper alternatives that are more common, highly active, and stable 13 . In doing so, a key strategy to retrieve high‐performance OER catalysts hinges upon the availability of electrode materials, including carbon‐based nanomaterials, graphene, and metal oxides/selenides/sulfides 14–24 . Thus far, the scientific community is increasingly interested in porous nanostructure‐based electrode materials, given their high surface‐to‐volume ratio, large and well‐defined pore structure, and even distribution of available active sites.…”
Section: Introductionmentioning
confidence: 99%
“…28 The results indicated that the co-existence of Fe/Co N sites and core-shell structure could significantly promote the ORR. Nevertheless, the aforementioned catalysts were typically synthesized by using complicated heat treatment of transition metals with macrocyclic nitrogen complexes, [29][30][31][32] Prussian blue analogs 33,34 and ionic liquids [35][36][37] which could be too expensive to be practically utilized.…”
Section: Introductionmentioning
confidence: 99%
“…The local coordination environment, electronic structure, or surface area of single‐metal containing catalyst can be adjusted by doping with one or more elements. For example, Shen and co‐workers constructed an electrode of Ni X Co 3‐X O 4 @NF, in which Co sites play an important role for its excellent OER activity and hollow structure of the electrocatalyst accelerate the bubble release, thus improving the OER performance [49] . Yin et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Shen and co-workers constructed an electrode of Ni X Co 3-X O 4 @NF, in which Co sites play an important role for its excellent OER activity and hollow structure of the electrocatalyst accelerate the bubble release, thus improving the OER performance. [49] Yin et al prepared a Co-Ni 0.2 Mo 0.8 N porous nanowires@NF electrode and the electrical conductivity and surface area of the three-metal nitride catalyst were improved due to the Co-doping, which led to the higher performance for OER, ORR (oxygen reduction reaction), and HER (hydrogen evolution reaction). [50] Liu et al reported a hollow spherical trimetallic phosphide P-CoNiFe@ glassy carbon electrode with splendid OER activity.…”
Section: Introductionmentioning
confidence: 99%